Organizational Behavior of the John Birch Society and Americans for Democratic Action, 1965 - Grupp, Frederick W. Jr ([Verlag nicht ermittelbar], 1984)
This study, conducted in 1965, collected data from 650 members of the John Birch Society, and 769 members of Americans for Democratic Action. Respondents were asked to name the magazines, news columnists, and television news programs that they were most familiar with, and to list all groups they belonged to, specifying their position in those groups. In addition, the respondents were queried on needs for improvements in the government. Demographic information includes sex, age, race, income, occupation, and religion. The data were received from the Social Science Data Center at the University of Connecticut.